Keadaan Gerakan Keluarga Berencana Di Desa Parlondu Kecamatan Pangururan Kabupaten Samosir - Lasriana Sinurat; Mbina Pinem (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2017)
The purpose of this research is to know the condition of family planning movement in terms of age, education, occupation, culture, and service quality of family planning acceptors in Parlondut Village, Pangururan District, Samosir District. The population is a married couples (PUS) who have been married for at least 5 years and already have children, and the sample is 40 people. Data collection techniques use interview lists and qualitative descriptive analysis techniques. Result: 1) Most of EFA (47,50%) have married age 25-29 years old with number of children more than two people, 2) In general, EFA (55,00%) have high school education with children more than 2 people 3 ) In general (37.50%) EFA mothers work in non-agricultural sectors as fish, tailor, IRT, traders, weavers with more than 2 children, 4) Batak culture has an influence in the EFA mindset about value and the number of children as the successor of the clan (100%) 5) there are 6 Quality of acceptor service of KB which influence to the non-success of family planning movement that is less appropriate method of contraception in the form of injection (35,00%) on self recommendation (67,50%) , less effective service mechanism performance (82,50%) with non-routine socialization / counseling (1-9 times in a year), so that the number of EFAs who have children more than 2 people and unable to follow family planning movement.